Perancangan Sistem Informasi Pelayanan Kantor Desa Selat Kabupaten Batang Hari Berbasis Website - Anggelia, Bella; Baharsyah, Bastomi; Triadi, Albet (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The aim of this research is to design a website-based service information system for the Selat Village Office, Batang Hari Regency. This research was conducted with a qualitative approach and with hardware and software tools. The results of this research show that the website-based service information system for the Selat Village Office, Batanghari Regency is designed using the Larevel framework with the PHP programming language and MySQL DBMS and has an online mail management feature which makes it easier for residents not to have to come to the office directly, and can disseminate information on administrative services. population quickly and widely by accessing the website, making it easier for residents to get the latest information without having to go to the office directly and the admin can provide a quick response by replying and resolving complaints.